2022
DOI: 10.1177/00048674221134510
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric service delivery for older people in hospital and residential aged care: An updated systematic review

Abstract: Objective: To review studies reporting on the effectiveness of psychiatry service delivery for older people and people with dementia in hospital and residential aged care. Methods: A systematic search of four databases was conducted to obtain peer-reviewed literature reporting original research published since June 2004 evaluating a psychiatry service for older people (aged 60 years and over) or people with dementia in inpatient or residential aged care settings. Results: From the 38 included studies, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Integrated CLP teams for older adults are preferred over POA in-reach models and split or shared POA/CLP arrangements because of their greater coherence, responsiveness and relationships across the general hospital and their potential to improve outcomes and reduce healthcare costs for older adult inpatients with comorbidities. Although in light of the current evidence base (Cations et al, 2022), the effectiveness of this approach will need to be tested with further research.…”
Section: Synthesis and Recommendationsmentioning
confidence: 99%
“…Integrated CLP teams for older adults are preferred over POA in-reach models and split or shared POA/CLP arrangements because of their greater coherence, responsiveness and relationships across the general hospital and their potential to improve outcomes and reduce healthcare costs for older adult inpatients with comorbidities. Although in light of the current evidence base (Cations et al, 2022), the effectiveness of this approach will need to be tested with further research.…”
Section: Synthesis and Recommendationsmentioning
confidence: 99%
“…3 Recent evidence suggests that POA inpatient care is effective in improving neuropsychiatric symptoms, mood, anxiety, and quality of life in older adults. 4 A exploratory study has also shown a potential causal relationship between late-life suicide rates and mental healthcare expenditure and the number of psychiatric beds and psychiatrists. 5 However, in New Zealand acute POA inpatient beds and clinical staff time were found to be funded differently across districts, 6 leading to a “postcode lottery” of care.…”
mentioning
confidence: 99%